Climate‑driven Internal Displacement and Social Cohesion in Libya’s Coastal Cities - Alriteemi, Abraheem; Abdullah, Mahmoud; Kasheem, Majdy; Masoud, Mohieddin (Lafadz Jaya Publisher, 2025)
Climate change is increasingly recognized as a major driver of internal displacement, particularly in fragile states like Libya where environmental shocks intersect with political instability and weak governance. This study investigates how climate-induced internal displacement affects social cohesion in Libya’s coastal cities, focusing on Tripoli, Misrata, and Benghazi. Using a qualitative research design, data were collected through in-depth interviews, focus group discussions, and field observations involving internally displaced persons (IDPs), host community members, and local stakeholders. Findings reveal that environmental factors such as drought and flooding have forced vulnerable populations to migrate from Libya’s interior regions to urban coastal centers. These displacements have strained public services, exacerbated competition for resources, and led to growing tensions between displaced populations and host communities. Social trust, mutual support, and access to services have all been undermined, while IDPs often face legal invisibility, psychological stress, and marginalization. Despite these challenges, the research identifies promising local initiatives that have fostered integration and rebuilt social ties, including joint livelihood programs and inclusive municipal governance efforts. However, these efforts remain fragmented and unsustainable without broader policy support. The study concludes that to prevent further erosion of social cohesion, Libya must adopt a national legal framework to recognize and protect climate-displaced persons, strengthen municipal capacities, and integrate displacement considerations into urban planning and climate adaptation strategies. This article contributes to emerging literature on climate migration and urban resilience by providing grounded, context-specific insights into how environmental displacement reshapes the social fabric in post-conflict settings.